2002
DOI: 10.1038/sj.ejhg.5200843
|View full text |Cite
|
Sign up to set email alerts
|

High resolution mapping of quantitative trait loci by linkage disequilibrium analysis

Abstract: Two methods, linkage analysis and linkage disequilibrium (LD) mapping or association study, are usually utilised for mapping quantitative trait loci (QTL). Linkage mapping is appropriate for low resolution mapping to localise trait loci to broad chromosome regions within a few cM (510 cM), and is based on family data. Linkage disequilibrium mapping, on the other hand, is useful in high resolution or fine mapping, and is based on both population and family data. Using only one marker, one may carry out single-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
39
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 21 publications
(17 reference statements)
2
39
0
Order By: Relevance
“…1,7,8 This article generalizes our previous work to extended multigeneration pedigrees of any sizes and any types of relatives. Intuitively, large pedigrees contain more linkage and LD information.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…1,7,8 This article generalizes our previous work to extended multigeneration pedigrees of any sizes and any types of relatives. Intuitively, large pedigrees contain more linkage and LD information.…”
Section: Introductionmentioning
confidence: 93%
“…Such as in Appendix B, Fan and Xiong, 1 we can show that the coefficients of regression equation (1) are given by…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By extending SKAT and SKAT-O to perform meta-analysis, Lee et al (2013) developed meta-analysis SKAT and SKAT-O (MetaSKAT and MetaSKAT-O) to carry out meta-analysis for rare variants in multiple studies. Both SKAT and MetaSKAT are score tests based on mixed-effect models.The third type is tests based on fixed-effect models that include (1) traditional additive effect models that are well studied (Cordell and Clayton 2002;Fan and Xiong 2002;Fan et al 2006) and (2) functional regression models as shown in our previous research (Luo et al 2012;Fan et al 2013Fan et al , 2014Wang et al 2015). Note that functional regression models are fixed-effect models, which extend traditional population genetics models to analyze multiple genetic variants and can analyze rare variants, common variants, or combinations of the two.…”
mentioning
confidence: 99%